Baseline Survey : Labor Market Outcomes of Punjab TEVTA Graduates - World Bank (Washington, DC, 2014)
Increasing employment among youth and increasing the earnings and job-stability of youth is important for Pakistan. This study examines the labor market outcomes of graduates from training institutes run by Punjab Technical Education and Vocational Training Authority (TEVTA), the largest technical and vocational education and training provider in the province of Punjab, Pakistan. The study uses an SMS-based survey of 7,840 graduates from 2010. This is a promising and inexpensive method to assess the impact of education and training in developing countries. Using SMS is feasible, fast, and very low-cost, but it comes with a set of challenges, notably a low response rate. The author summarizes lessons for future SMS-administered surveys. For the labor market outcomes, we find that only 39 percent of graduates are employed post training with considerable variation in employment outcomes across trades, districts, gender, and schools. The author conclude that there is overall strong need for the improvement of quality and relevance of technical education and vocational training, and that some schools, trades, and districts are substantially better at linking to labor market demand than others.